Surgical Management of Intracranial Epidermoid Tumors—An Institutional Review of 234 Cases - Velho, Vernon; Bhide, Anuj; Naik, Harish; Jain, Nimesh (Indian Journal of Neurosurgery, 2019)
Aim To study the demographics, clinical profile, management strategies, and treatment outcomes of intracranial epidermoid lesions.Materials and Methods A single institutional retrospective analysis from a large institute in Western India was done of all patients operated for intracranial epidermoid tumors over a period of 20 years from January 1997 to January 2017. All patients were investigated with a contrast-enhanced computed tomography (CECT) as well as a magnetic resonance imaging (MRI), with a diffusion-weighted imaging to confirm diagnosis of epidermoid tumor. The presenting complaints and the demographics of all patients were recorded, and all patients underwent planned surgery, with or without a cerebrospinal fluid (CSF) diversion procedure as per requirement. Surgery ranged from a gross total resection to a near-total resection depending on the patient, location of the lesion, and involvement of adjacent structures. All patients underwent an immediate postoperative computed tomographic (CT) scan as well as a follow-up MRI. Patients were followed up to note clinical improvement as well as documentation of all complications.Results Total 234 patients of intracranial epidermoid tumors were operated upon in a 20-year span. Males predominated with a total number of 146 (62.4%). The most common age group was the fourth decade. The most common presentations were headache (118 patients) and neuralgia in the trigeminal distribution (82 patients). Infratentorial compartment was the most common location of the tumors (152 patients), with cerebellopontine angle being the predominant site in the posterior fossa (107 patients). Both supra- and infratentorial compartments were involved in 28 cases. Gross total excision could be achieved in 202 patients. Reoperation was required in 12 cases. The mean follow-up period was 68 months. The most common complication encountered was that of postoperative CSF leak (24 patients). We had eight cases of recurrence and six deaths in our series.Conclusion Epidermoid tumors can arise in virtually all intracranial locations. Gross total excision of the tumor is treatment of choice and can be curative for these benign lesions. Large lesions at presentation with involvement of multiple compartments can be difficult to manage and may require bicompartmental or second look surgery. Complete excision of the capsule with preservation of adjacent neuronal and vascular structures is of utmost importance to decrease postoperative morbidity and chances of recurrence. Perioperative steroids, avoidance of intraoperative spillage, and intraoperative endoscopic assistance are recommended in all cases.
Keywords: epidermoid tumor; infratentorial; supratentorial; cerebellopontine angle; surgical outcomes